Neuroimaging Techniques for Neuroplasticity Quantification in Stroke Patients - Rodríguez-García, Martín Emiliano; Marín-Arriaga, Norma; Macías-Arriaga, Silvia Gabriela; Salazar-Cárdenas, Bernardo; Ramírez-Rodríguez, Tania; Aparicio-Jiménez, Víctor Hugo; Valdés-Cristerna, Raquel; Cantillo-Negrete, Jessica (Revista Mexicana de Ingenieria Biomedica, 2023)
Neuroimaging techniques provide relevant information of the functional and anatomical status of the human brain. This information is of particular importance when a pathology, like stroke, produces a brain injury. In stroke patients, it has been determined that neuroplasticity is the primary recovery mechanism of the lost motor function. Due to worldwide high prevalence, especially in developing countries, it is necessary to continue the research of the recovery mechanisms involved in this pathology. To this end, functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) are two of the most used neuroimaging techniques. In stroke patients, fMRI allows the analysis of the neural activity produced by the execution of motor tasks, whereas DTI provides structural information of the brain anatomy. In this narrative review, multiple studies that employ these neuroimaging techniques for quantification of neuroplasticity changes in stroke patients after undergoing a neurorehabilitation program are presented. Better understanding of these neuroplasticity changes would allow researchers to design and provide more beneficial rehabilitation schemes to stroke patients.